Modified predator-prey algorithm approach to designing a cooling or insulating skylight. (December 2017) - Fält, Martin; Pettersson, Frank; Zevenhoven, Ron
Abstract: Both cooling and thermal insulation can be achieved using a triple-glazed skylight filled with a gas that absorbs and emits thermal radiation. Utilizing radiative cooling as the driving force a cooling effect can be achieved in the here outlined skylight, while it can also act as a thermal insulator when desired. Inside the skylight the gas it contains circulates by natural convection induced by its heated lower compartment to the radiatively cooled upper compartment that "sees" the sky. By this circulation, cooling is obtained to a room located below the skylight. When this circulation is cut off, the skylight acts as a thermal insulator. This gives a multi-objective optimization problem, as these two objectives are conflicting. In this article, a Pareto front is created that shows possible trade-off solutions between the cooling and insulating properties of the designed skylight. This Pareto front is created by optimizing the dimensions of the skylight. Thus, the skylight will provide an optimal cooling effect and an optimal insulation effect when needed. Graphical abstract: Highlights: A skylight design was optimized for both its cooling and insulation properties. Materials were identified that improve the performance of the skylight. A modified version of the multiobjective predator-prey algorithm was created.